2000
DOI: 10.1179/136217100101538452
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of vermicular and lacy ferrite in austenitic stainless steel weld metals

Abstract: Solidification and subsequent transformation of austenitic stainless steel weld metals that solidified in the ferritic–austenitic mode were investigated from the viewpoint of crystallography. The formation mechanisms for the vermicular and lacy ferrite observed in the weld metals were clarified. The ferrite morphology is determined by both the crystallographic orientation relationship between ferrite and austenite established at the stage of ferrite nucleation and the relationship between the welding heat sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 15 publications
0
30
0
5
Order By: Relevance
“…Naturally, these results correspond to those of the X-ray diffraction. These results for the growth mode of the secondary phase may also correspond to those of the microstructure observation of the liquid-tin quenched metal by Inoue et al 11,12) …”
Section: Srxrdmentioning
confidence: 64%
See 1 more Smart Citation
“…Naturally, these results correspond to those of the X-ray diffraction. These results for the growth mode of the secondary phase may also correspond to those of the microstructure observation of the liquid-tin quenched metal by Inoue et al 11,12) …”
Section: Srxrdmentioning
confidence: 64%
“…So the solidification morphology of the weld metal has been estimated by the SEM observation of microstructure, using the liquid-tin quenching method. [10][11][12] In late nineties, Elmer et al [13][14][15] has been used a intense synchrotron radiation as a probe and directly revealed the phase mapping around the heat spot, during pure titanium welding. After that, Babu et al investigated the primary weld solidification in the Fe-C-Al-Mn weld steel [16][17][18] using the Time-Resolved X-Ray Diffraction (TRXRD) technique.…”
Section: Introductionmentioning
confidence: 99%
“…So the solidification morphology has been observed by the Scanning Electron Microscope (SEM), using the liquid-tin quenching method in high alloys that have some influence on solid-transformation. [1][2][3] Since late nineties, Elmer et al [4][5][6] has used intense synchrotron radiation and has directly revealed the phase mapping around the heat source, during pure titanium welding. After that, Babu et al investigated the primary weld solidification in the Fe-C-AlMn steel weld [7][8][9] using the Time-Resolved X-Ray Diffraction (TRXRD) technique.…”
Section: Introductionmentioning
confidence: 99%
“…Em função das características citadas anteriormente, intrínsecas ao material, podem ser retidas quantidades variáveis de ferrita  (delta) a temperatura ambiente (INOUE, 2000;MODENESI, 2001).…”
Section: Microestrutura Da Zona Fundidaunclassified
“…Uma análise prévia no modo de solidificação das fases do aço inox austenítico poderá então ajudar a prevenir falhas como suscetibilidade a trincas e melhorar a resistência a eventuais trincas (INOUE, 2000;MODENESI, 2001;SHANKAR, 2003).…”
Section: Microestrutura Da Zona Fundidaunclassified